U-Th disequilibrium, (U-Th)/He and 40Ar/39Ar geochronology of distal Nisyros Kyra tephra deposits on Datça peninsula (SW Anatolia) - Gençalioğlu-Kuşcu, Gonca; Uslular, Göksu; Danišík, Martin; Koppers, Anthony; Miggins, Daniel P.; Friedrichs, Bjarne; Schmitt, Axel Karl (Quaternary geochronology, 2020)
Kyra is an important tephra unit for Nisyros pre-caldera stage due to a number of subunits with various compositions (basaltic andesite to dacite) and distal dispersion on surrounding Greek islands (Tilos and Chalki) and Datça peninsula (Turkey). As for the most Nisyros tephra units, the available radiometric ages of Kyra tephra are not compatible with the relatively well-established Nisyros tephrostratigraphy. This beclouds the characterization of both proximal and distal Kyra tephra and also the understanding of Nisyros pre-caldera volcanism. In order to provide new insight into Nisyros tephrochronology, we here present the first (U-Th)/He and 40Ar/39Ar ages of Kyra distal andesitic pumice previously reported on Datça peninsula. (U-Th)/He dating of apatite (DZS pumice, Sındıköy) yielded weighted mean ages of 134.8±19.8 ka (2σ, single-crystal aliquots, n=12, MSWD=0.21) and 139.6±15.0 ka (2σ, multi-crystal aliquots, n=5, MSWD=0.78). Combined U-Th disequilibrium and (U-Th)/He dating of zircon (DZS pumice) yielded an age of 131.1±8.6 ka (2σ, single-crystal aliquots, n=8, MSWD=0.58). The inverse isochron 40Ar/39Ar age of DAH (Hızırşah) pumice (plagioclase, 135.7±28.2 ka, 2σ, MSWD=1.70) is almost comparable with the (U-Th)/He ages, while the plateau ages of DAB (Belen) pumice are relatively older (plagioclase, 144.8±26.6 ka, 2σ, n=17, MSWD=0.61; hornblende, 151.5±19.5 ka, 2σ, n=27, MSWD=1.41). DAB pumice has also more evolved glass composition (mainly dacitic) compared to andesitic DAH and DZS pumice. Therefore, DAB tephra is considered as a different Kyra subunit. All new ages on distal Kyra tephra are in accordance with the Nisyros tephrostratigraphy and indicate a long-lasting eruptive history (~20 ka) of the tuff cone that formed Kyra sequence. Considering the available ages for the Kos Plateau Tuff (KPT) eruption (161 or 165 ka) and the presence of stratigraphically older Nisyros tephra units than Kyra, there should be no significant time gap between the KPT eruption and the onset of Nisyros subaerial volcanism. In addition, the recent findings on distal Kyra tephra will probably provide new opportunities for correlating the undefined tephra units that have comparable composition and age reported in both marine and terrestrial settings. Thus, our study will indirectly contribute to paleoenvironmental/climatological and tephrochronology studies around the Mediterranean region.
40 und 39 im Titel sind hochgestellt
Available online 28 October 2019
Gesehen am 30.06.2021